Levels of Service Skills for Athletes Club North Indralaya - Ragil Aji Pangestu; Rury Rizhardi; Siti Ayu Risma Putri; Suyatno; Nevy Anggraeni; Muhammad Eka Rio (Universitas PGRI Palembang, 2023)
The problem in this research is that the level of passing skills for volleyball is not known in the North Indralaya sub-district. This study aims to determine the Level of Service Skills for Volleyball at the Athlete Club of North Indralaya District. The variable in this study is a single variable, namely service skills on volleyball. The population in this study were soccer athletes, totaling 20 athletes, while the sample was taken using a total sampling technique so that all populations were sampled in this study. The method in this research is descriptive quantitative with a survey approach. Data collection techniques using the above service test instrument. Data analysis using the Percentage Formula. The results showed that the level of top service skills at the volleyball club in North Indralaya District showed that the athletes who had good categories were 13 athletes (65%) of which 7 athletes from the Cambodian volleyball club and 6 athletes from the Mawar volleyball club, which had sufficient 4 athletes (20%) where 2 athletes from the Cambodia volleyball club and 2 athletes from the Mawar volleyball club, who have a less category 2 athletes (10%) where 1 athlete from the Cambodia volleyball club and 1 athlete from the Mawar volleyball club, and who has a bad category of 1 athlete (5%) from the Mawar volleyball club. It was found that the athlete's score showed an average of top service skills at the volleyball club in North Indralaya District of 38.01. The average value of the second club shows that the service skills on the ball are in the sufficient category.